-7(f+1)=5(f-2)

Simple and best practice solution for -7(f+1)=5(f-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(f+1)=5(f-2) equation:


Simplifying
-7(f + 1) = 5(f + -2)

Reorder the terms:
-7(1 + f) = 5(f + -2)
(1 * -7 + f * -7) = 5(f + -2)
(-7 + -7f) = 5(f + -2)

Reorder the terms:
-7 + -7f = 5(-2 + f)
-7 + -7f = (-2 * 5 + f * 5)
-7 + -7f = (-10 + 5f)

Solving
-7 + -7f = -10 + 5f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-5f' to each side of the equation.
-7 + -7f + -5f = -10 + 5f + -5f

Combine like terms: -7f + -5f = -12f
-7 + -12f = -10 + 5f + -5f

Combine like terms: 5f + -5f = 0
-7 + -12f = -10 + 0
-7 + -12f = -10

Add '7' to each side of the equation.
-7 + 7 + -12f = -10 + 7

Combine like terms: -7 + 7 = 0
0 + -12f = -10 + 7
-12f = -10 + 7

Combine like terms: -10 + 7 = -3
-12f = -3

Divide each side by '-12'.
f = 0.25

Simplifying
f = 0.25

See similar equations:

| -6x-13=x-23 | | x-y=31 | | x^2-6x-4=8 | | (2x+9)+x=90 | | -27.4=p-8.8 | | x+(3*3*3)=3*X-(10*10) | | 0.5(8x-16)=0.666(6x+12) | | h=1+30t-5t^2 | | sqrt(x)-4=2-x | | x^7/5=4 | | 12=-(6-6a)-3(a-6) | | 128=4k+5(6+2k) | | 10y^15+40y^10+25y^8= | | 4(2x+3)=6-(3-2x) | | d=-16t^2-2t+815 | | 40=8/5y | | -19.7=-8.4+x | | 4z+11=3-11 | | D+4(d+6)=11 | | 98-0.54t=80 | | 2cosx=sin(x+30) | | 5x-9x=-16 | | -49=3x+3x+5 | | 98-0.54t=2+0.54t | | 43000000(0.095)= | | 56x+21= | | 3x-6+5x=-86 | | [x-3]=3x+1 | | 3x-12x=-4 | | y=2/3x^2-1/6x-4=0 | | 6x^2-19x+6=0 | | 1/3(x-2)=2x-13/3 |

Equations solver categories